Evaluation of the presence of myofibroblasts and matrix metalloproteinase 1 expression in the stroma of oral verrucous hyperplasia and verrucous carcinoma - Nazanin Mahdavi; Pouyan Aminishakib; Parisa Nabiyi; Alireza Ghanadan; Maedeh Ghorbanpour; Merva Soluk-Tekkesin (Wolters Kluwer Medknow Publications, 2020)
Background: Oral verrucous carcinoma is a low-grade subtype of oral squamous cell carcinoma that should be differentiated from oral verrucous hyperplasia, a premalignant lesion. Stromal activated myofibroblasts known as cancer-associated fibroblasts have an active role in the initiation and progression of the cancers via secretion of different molecules including matrix metalloproteinases. Aims: This study is designed to understand the differences in the presence of myofibroblasts and expression of matrix metalloproteinase-1 in the adjacent stroma of verrucous carcinoma and oral verrucous hyperplasia (OVH). Settings and Design: Cross-sectional study. Material and Methods: Twenty-seven OVH, 19 oral verrucous carcinoma (OVC), and 8 cutaneous verrucous carcinoma (CVC) specimens were analyzed for immunohistochemical (IHC) expression of α-smooth muscle actin (αSMA) and MMP-1. Results: IHC studies for αSMA expression in nonvascular stromal cells of the adjacent stroma revealed mild or no expression in 81.4%, 73.7%, and 62.5% of the cases of OVH, OVC, and CVC groups, respectively. No significant difference was seen in αSMA expression index between OVH and OVC groups (Adj. Sig. = 0.220) and between OVC and CVC groups (Adj. Sig. = 1.00). Pairwise analysis revealed a significant difference in MMP-1 expression index between the groups. No significant correlation was observed between MMP-1 expression index and αSMA expression index in OVH (pv = 0.358) and OVC (pv = 0.388) groups. Conclusion: The differences in MMP-1 expression between OVH and OVC can be used as an adjunctive aid in challenging cases including disoriented or inadequate samples.